Advances in Human Factors in Robots and Unmanned Systems : Proceedings of the AHFE 2018 International Conference on Human Factors in Robots and Unmanned Systems, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA /: Proceedings of the AHFE 2018 International Conference on Human Factors in Robots and Unmanned Systems, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA. (2018) - Unknown
No abstract available